The Mechanism of Ajmaline and Thus Brugada Syndrome: Not Only the Sodium Channel! - Monasky, Michelle M.; Micaglio, Emanuele; D'Imperio, Sara; Pappone, Carlo (Frontiers in Cardiovascular Medicine, 2021)
Ajmaline is an anti-arrhythmic drug that is used to unmask the type-1 Brugada syndrome (BrS) electrocardiogram pattern to diagnose the syndrome. Thus, the disease is defined at its core as a particular response to this or other drugs. Ajmaline is usually described as a sodium-channel blocker, and most research into the mechanism of BrS has centered around this idea that the sodium channel is somehow impaired in BrS, and thus the genetics research has placed much emphasis on sodium channel gene mutations, especially the gene SCN5A, to the point that it has even been suggested that only the SCN5A gene should be screened in BrS patients. However, pathogenic rare variants in SCN5A are identified in only 20-30% of cases, and recent data indicates that SCN5A variants are actually, in many cases, prognostic rather than diagnostic, resulting in a more severe phenotype. Furthermore, the misconception by some that ajmaline only influences the sodium current is flawed, in that ajmaline actually acts additionally on potassium and calcium currents, as well as mitochondria and metabolic pathways. Clinical studies have implicated several candidate genes in BrS, encoding not only for sodium, potassium, and calcium channel proteins, but also for signaling-related, scaffolding-related, sarcomeric, and mitochondrial proteins. Thus, these proteins, as well as any proteins that act upon them, could prove absolutely relevant in the mechanism of BrS.